Feasibility Study of an Alcohol-Based Liquid Scintillation Detector and Its Application - Byoung Chan Kim; Ji Young Choi; Kyung Kwang Joo; Seon Yeong Park; Ye Sung Song; Hee Jin Woo (Advances in High Energy Physics)
This paper proposes a new base material, a mixture of alcohol and water, for liquid scintillators. A possibility of using alcohol as a new detection solution in a particle detector is described. A liquid scintillator is widely used in various fields because of its high light yield. In addition, it is very important to develop a stable liquid scintillator for particle detectors or other medical applications. To date, there have been no previous R&D studies elsewhere for the use of alcohol in particle detectors, and no market products are available of this type. Thus, there is a room for improvement. This paper describes the brief synthesizing process of the alcohol-based liquid scintillator by varying the mixing ratio of each component that makes up the liquid scintillator. The several feasible physical and optical properties of an alcohol-based liquid scintillator were investigated and presented. Finally, as one of its applications, a range (beam-path length) measurement using an electron beam in medical physics is introduced after irradiating an alcohol-based liquid scintillator with electron beam energies of 6~12 MeV. The measurement results were compared with a Monte Carlo simulation, Novalis Tx, a phantom, and a CT image. In the near future, the new alcohol-based liquid scintillator could be used for particle detector or medical imaging applications.